Breeding potential of Spanish bread wheat landraces: genetic variability in vernalization and photoperiod sensitivity - Giménez, Estela; Pascual, Laura; López-Fernández, Matilde; Vázquez-García, José G.; García-Mondejar, Marta; Ruiz, Magdalena; Giraldo, Patricia (Frontiers in Plant Science, 2025)
Flowering time and grain filling, regulated by temperature-responsive (vernalization) and day length (photoperiod) genes, are critical factors in wheat production. In this study, we analyzed genetic variation at the VRN-A1, VRN-B1, PPD-A1, PPD-B1, PPD-D1, EPS-A1, EPS-D1, and WAPO-A1 loci in 188 Spanish wheat landraces and compared them to 28 modern cultivars. Growth habit and phenological traits (days to heading and maturity) were assessed in field trials, and the impact of genetic variability on these traits was evaluated. Our results revealed distinct genetic diversity patterns between landraces and modern cultivars and confirmed that the absence of spring alleles at VRN1 loci was necessary for a winter growth habit. Dominant alleles from VRN1 gene (Vrn-A1a, Vrn-A1b, Vrn-B1a) and photoperiod-insensitive alleles from PPD1 gene (Ppd-B1a, Ppd-D1a) consistently promoted early heading and flowering, despite genotype-by-environment (G×E) interactions. Interestingly, Ppd-D1b allele, although classified as photoperiod-insensitive exhibited, delayed flowering likely due to its molecular variation. While allelic variation at EPS1 locus had no significant impact on phenology, results suggested a potential role for WAPO1 in flowering regulation. Our findings highlight the genetic diversity within Spanish wheat landraces, offering valuable genetic resources for optimizing flowering time and improving wheat adaptation to complex agro-climatic conditions.